Performance Contracting as a Paradigm Shift in the Utilization of Teaching & Learning Resources: Perceptions of Tutors in Technical Institutes in Rift Valley, Kenya. - Manwa, Mosomi B.; Dorcas, Okindo (KABARAK UNIVERSITY, 2012)
Every year thousands of students leave the regular formal educational institutions in Kenya, but they cannot progress to higher levels of formal education. Despite past investments in Kenya’s Technical, Industrial, Vocational Education and Training (TIVET) subsector, many school leavers fail to access TIVET. This is because the subsector is said to be facing many challenges related to wastage of resources, irrelevant training and turnover of personnel. The government of Kenya introduced performance contract signing in the year 2004. The performance contracts were aimed at improving resource utilization in public institutions among other objectives. This study sought to establish the perceptions of Kenyan tutors in Technical Institutes in Rift Valley about the impact of performance contracts as a paradigm shift on the utilization of teaching and learning resources. The study adopted a survey strategy. The study population comprised of tutors, Heads of Department and Principals of Technical Institutes in Rift Valley. The stratified random sampling technique was applied in the selection of the study sample. This involved the grouping of tutors into 8 strata according to the available departments. Thereafter the proportionate random sampling technique was applied to get an equal proportion of respondents from each stratum. The purposive random sampling technique was used to sample the heads of department and principals. Questionnaires and interviews were used to collect data. This entailed the supplying of quest ionnaires to tutors, heads of department and principals of the sampled Technical Institutes. Interviews were conducted with principals of the sampled institutions. The data collected were analyzed by use of descriptive statistics. The findings of the study revealed that performance contracting had not led to tutors being trained on the proper utilization of learning and teaching resources. The study concluded that financial constraints hindered tutors from being trained on the utilization of modern learning and teaching resources. The study recommends that the gains made in the implementation of the performance contracting strategy should be strengthened with the availing of more financial resources to ensure that the required learning & teaching resources are all made available. The findings would help education policy makers to address the issue of performance contracts from an informed position as well as get insight on how to apply performance contracts in the optimum utilization of resources.
Keywords: Paradigm shift; Performance contracting; Resource utilization; Teaching and learning